2015
DOI: 10.1002/pc.23858
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermo‐mechanical, thermal, and swelling properties of EPDM‐organically modified mesoporous silica nanocomposites

Abstract: Ethylene-propylene-diene terpolymer nanocomposites has been developed using organically modified mesoporous silica nanoparticles by solution blending method. Hydrophilic mesoporous silica nanoparticles (MCM-41) of 100 nm in sizes were synthesized via a template-directed method, functionalized with trimethylchlorosilane (TMS) to produce hydrophobic silica (OS). The X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) analysis suggest that OS are homogeneously di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
1
3
1
Order By: Relevance
“…The possible reason for this observation was the incorporation of organic moieties within the mesopores of silica. Similar observations have been reported in the literature. …”
Section: Resultssupporting
confidence: 92%
“…The possible reason for this observation was the incorporation of organic moieties within the mesopores of silica. Similar observations have been reported in the literature. …”
Section: Resultssupporting
confidence: 92%
“…It is showed that, compared with EPDM, the tensile strength of DV‐DDSQ and DH‐DDSQ modified EPDM increased by 35.8% and 55.3% respectively, the tear strength was increased by 6.4% and 5% respectively, meanwhile the elongation at break were somewhat unchanged. Compared with the mechanical properties of EPDM previously reported, 1,12,13,29 the strength and elasticity of brPOSS /EPDM remained at a higher level. Generally speaking, strength and elasticity as important parameters to evaluate the mechanical properties of elastomer, the elongation at break normally decrease with the rise in the strength, therefore it is difficult to ensure the both increase of elasticity and strength simultaneously 16,36,37 .…”
Section: Resultscontrasting
confidence: 68%
“…Simultaneously, the presence of glass microspheres increased the flammability of the resulting formulation. Acharya H et al 12 prepared hydrophobic silica (OS)/EPDM, the results showed that the tensile strength of materials which incorporated of OS nanoparticle with 3 and 10 wt% is 3.95 MPa and 1.67 MPa respectively, and the elongation at break is 229% and 174% respectively, and the carbon residual rate at 600°C is 2.7% and 7.25%. Haijuan Kong et al 13 grafted silica onto aramid pulp (AP) surface, and SiO 2 ‐AP/EPDM were then prepared.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The use of nanoparticles has attracted considerable attention among the scientists to overcome these issues. The most widely used nanoparticles in the literature are carbon nanotubes (CNTs), [3][4][5][6][7][8][9][10] silica, [11][12][13] clay, [14,15] graphene [16][17][18] and their hybrids. [19][20][21] However, the use of carbon-based nanoparticles is restricted in the aerospace industry due to various drawbacks such as their high cost and significant toxicity to the environment and human health.…”
Section: Introductionmentioning
confidence: 99%